Pengaruh Harga Terhadap Keputusan Pembelian Air Rebus Pada CV. AFNA Di Langsa - Manurung, M. Afandi; Refi , T. Muana (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2023)
This research was carried out at boiled water producer CV. Afna Langsa took a sample of 70 respondents, namely customers. The distribution of questionnaires was carried out from October 2017 to November 2017 as primary data which was then analyzed using simple linear regression analysis equipment, then hypothesis testing was carried out using the t test, testing the correlation coefficient and coefficient of determination. Price is the amount of money sacrificed for an item or services, or value from consumers in exchange for benefits or ownership or use of products or services. Meanwhile, purchasing decisions are one of the main components of consumer behavior. Consumer purchasing decisions are the steps used by consumers when purchasing goods and services. Based on the results of simple linear regression, it is found that Y=4.531+0.672X, a constant of 4.531 is the value of the Purchase Decision variable when the Price variable is zero, or if the value of the Price variable is increased by 1 then the value of the Purchase Decision variable will increase by 0.672. Meanwhile, testing the correlation coefficient (r) obtained 0.753, indicating a strong relationship between variables, and the coefficient of determination (r2) 0.567 or 56.7%, the remaining 43.3% is influenced by product quality, brand, promotion and service quality. In the results of hypothesis testing (t test), the significance level of the Price variable on Purchasing Decisions was obtained tcount > ttable or 9.428 > 1.994 and tsig < 5% or 0.00 < 0.05. Shows that price influences the decision to purchase boiled water at CV. Afna Langsa, thus the hypothesis is that price influences the decision to purchase boiled water at CV. Afna in Langsa City was accepted